2006
DOI: 10.1523/jneurosci.3507-06.2006
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Caspase-Mediated Apoptosis by Peroxynitrite in Traumatic Brain Injury

Abstract: In traumatic brain injury (TBI), neurons surviving the primary insult may succumb through poorly understood secondary mechanisms. In vitro, cortical neurons exposed to stretch injury exhibited enhanced vulnerability to NMDA, apoptotic-like DNA fragmentation, peroxynitrite (PN) formation, and cytoplasmic cytochrome c accumulation. Surprisingly, caspase-3 activity was undetectable by both immunoblotting and fluorogenic activity assays. Therefore, we hypothesized that PN directly inhibits caspases in these neuron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
49
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(54 citation statements)
references
References 81 publications
4
49
0
Order By: Relevance
“…Â area (1.49 in 2 ), we calculated that at 2.9 p.s.i., J (on cells) E9.6 N s. We have shown earlier that this sublethal trauma does not confer delayed cell death on its own -as assessed by propidium iodide uptake 20 h after injury -or alter membrane permeability, as assessed by carboxyfluorescein uptake and retention of fluorescein di-acetate. 9 This model is highly consistent with other paradigms of in vitro TBI in the literature, 30,32 which have frequently been used to delineate the intracellular mechanisms that contribute to progressive neuronal injury after mechanical trauma.…”
Section: Methodssupporting
confidence: 66%
See 1 more Smart Citation
“…Â area (1.49 in 2 ), we calculated that at 2.9 p.s.i., J (on cells) E9.6 N s. We have shown earlier that this sublethal trauma does not confer delayed cell death on its own -as assessed by propidium iodide uptake 20 h after injury -or alter membrane permeability, as assessed by carboxyfluorescein uptake and retention of fluorescein di-acetate. 9 This model is highly consistent with other paradigms of in vitro TBI in the literature, 30,32 which have frequently been used to delineate the intracellular mechanisms that contribute to progressive neuronal injury after mechanical trauma.…”
Section: Methodssupporting
confidence: 66%
“…We used the cells for experiments 11-14 days after isolation consistent with earlier in vitro stretch assays. 24,29,30 In vitro model of mild TBI. Before stretch, the culture medium was replaced with 2 ml HEPES buffered saline (concentrations in mM: 121 NaCl, 5 KCl, 20 glucose, 10 HEPES acid, 7 HEPES-Na salt, 3 NaHCO 3 , 1 Na-pyruvate, 1.8 CaCl 2 and 0.01 glycine, adjusted to pH 7.4 with NaOH).…”
Section: Methodsmentioning
confidence: 99%
“…Consistent with this hypothesis, it has been shown that ROS can inhibit calpain activity via oxidation of the sulfhydryl groups of cysteine residues at the active site of the enzyme (Benuck et al, 1992) (Guttmann et al, 1997) (Guttmann and Johnson, 1998). Recent work by another group has shown that another cysteine protease caspase-3 in the traumatized brain is similarly inhibited by PN specifically, and that this is prevented by application of the sulfhydryl reducing agent dithiothreitol (Lau et al, 2006). The latter is also relevant since the SBDP150 fragment which also showed a biphasic time course is partially generated by caspase 3 as well as calpain (Wang, 2000b).…”
Section: Interaction Of Peroxynitrite-induced Oxidative and Calpain-mmentioning
confidence: 79%
“…Alternatively, it might be that upregulation of caspases activation in HIBM cells does not result in a concordant upregulation of PS externalization, although this apoptotic phenomenon is known to be caspase dependent. 26 Interestingly, there is accumulating data pointing to caspaseindependent PS externalization occurring during apoptosis, for example in STS-treated primary T lymphocytes, 27 possibly indicating that in some conditions those two processes may be independently activated. Therefore, it may well be that caspases activation, but not PS externalization, is involved in HIBM pathology.…”
Section: Discussionmentioning
confidence: 99%